Skull repair implant, method of making and skull repair system
Patent Information
- Application Number
- CN202311856859.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-29
- Publication Date
- 2026-09-04
- Estimated Expiration
- 2043-12-29
AI Technical Summary
颅骨锁为滑动固定方式,可以适配儿童颅腔的生长动态变化,但因其结构特性,使得其在术中使用灵活性受限,可能对颅内结构造成损伤,且固定力不足可能造成术后颅骨修补体脱落;刚性固定一般为连接片配合固定钉,固定后不再具备动态滑动特性,此固定方式不能适配儿童颅腔的生长动态变化
[0040] The cranial repair implant of the present invention can achieve one-time fixation of inert bone implants, which is convenient to use, can shorten the operation time, and make the bone implantation process quick and convenient.
Smart Images

Figure CN120227503B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a cranial repair implant, its preparation method, and a cranial repair system, belonging to the field of medical materials. Background Technology
[0002] Cranioplasty is one of the most common surgeries in neurosurgery. Its main purpose is to restore the closure of the cranial cavity, prevent further brain tissue damage, and treat craniectomy syndromes. Currently, materials used for cranioplasty, besides autologous skull bone, include medical-grade titanium alloys, titanium mesh, hydroxyapatite, polymethyl methacrylate (PMMA), and polyetheretherketone (PEEK). During the procedure, cranial locks, connecting plates, and bone screws are typically used to connect and fix the cranioplasty body to the autologous skull. The surgery requires experienced surgeons to pre-determine the placement of the cranioplasty system and select appropriate fixation structures based on the specific situation. In some cases, temporary drilling may be necessary. The installation process is complex, time-consuming, and inefficient, causing significant inconvenience to the surgery.
[0003] Furthermore, before cranioplasty, patients usually need to undergo cranial CT and frontal bone X-ray examinations. Through digital molding, three-dimensional reconstruction, molding and processing, a cranioplasty prosthesis that matches the patient's bone defect can be manufactured, requiring high precision in the processing.
[0004] Furthermore, when performing cranioplasty on children or other patients with rapidly growing bones, the skull is still growing, thickening, and taking shape. A certain gap needs to be left between the cranioplasty prosthesis and the autologous bone suture to provide space for the growth of the bone window. However, most existing cranioplasty prostheses are designed for adults, lack expandability, and are not suitable for cranioplasty in children.
[0005] Furthermore, current cranioplasty primarily utilizes fixation components to expand the surgical space. These fixation components generally fall into two categories: sliding fixation and rigid fixation. Skull locks, a sliding fixation method, can adapt to the dynamic changes in a child's cranial cavity during growth. However, due to their structural characteristics, their flexibility during surgery is limited, potentially causing damage to intracranial structures. Insufficient fixation force may also lead to postoperative dislodgement of the cranioplasty. Rigid fixation typically involves connecting plates and fixation screws; once fixed, it no longer possesses dynamic sliding characteristics, and this fixation method cannot adapt to the dynamic changes in a child's cranial cavity during growth. Summary of the Invention
[0006] The problem the invention aims to solve
[0007] In view of the technical problems existing in the prior art, the present invention first provides a cranioplasty implant. The cranioplasty implant of the present invention can achieve one-time fixation of inert bone implants, is convenient to use, shortens surgical time, and makes the bone implantation process quick and convenient; for children or patients with changes in bone windows, a change window can be reserved, improving the long-term stability of the implant; furthermore, the cranioplasty implant of the present invention has relatively lower requirements for the contour of the bone window edge, reducing mismatch problems caused by design or processing precision, and can also induce edge bone window growth, accelerating bone fusion.
[0008] Furthermore, the present invention also provides a method for preparing a cranial repair implant, which is simple and easy to implement, uses readily available raw materials, and is suitable for mass production.
[0009] Solution for solving the problem
[0010] This invention provides a cranioplasty implant, comprising a main body made of polyaryletherketone, and having a through-hole; wherein,
[0011] The area extending within 1 cm from the edge of the main body towards its center is a porous region, which has multiple microporous structures. The gel fills these microporous structures to form a composite portion.
[0012] The gel extends beyond the edge of the main body to form a gel portion.
[0013] Furthermore, the area of the upper surface of the porous region is 10% to 70% of the area of the upper surface of the main body; and / or, the average pore size of the microporous structure is 0.5 to 5 μm.
[0014] Furthermore, the raw materials of the gel component include a first component, a second component, and a third component; wherein,
[0015] The first component comprises gelatin-coated bioactive particles, the surface of which contains primary amino and / or carboxyl groups; preferably, the particle size of the bioactive particles is 0.1–3.0 μm;
[0016] The second component comprises a biodegradable material having a primary amino group, preferably, the second component comprises one or more of gelatin, polyethyleneimine or polylysine;
[0017] The third component comprises a polysaccharide having functionalized groups, preferably including aldehyde groups and / or succinimide groups.
[0018] Furthermore, by mass, the ratio of the content of the first component to the sum of the contents of the second and third components is (3-7):(10-20);
[0019] The mass ratio of the second component to the third component is (0.8 to 2):1.
[0020] The present invention also provides a method for preparing a cranioplasty implant according to the present invention, characterized by comprising the following steps:
[0021] Step 1: A reserved area is formed within 1 cm from the edge of the skull repair matrix containing polyaryletherketone material to the center, and the reserved area of the matrix is pretreated to form a microporous structure to obtain a pretreated product.
[0022] Step 2: Fill the microporous structure of the reserved area with gel to form a composite part;
[0023] Step 3: Extend the gel beyond the edge of the substrate to form a gel portion, thereby obtaining a cranial repair implant.
[0024] Further, the pretreatment includes the steps of sulfonation and / or plasma treatment of the reserved area of the substrate; preferably, the pretreatment includes placing the reserved area in a sulfuric acid solution for sulfonation; more preferably, the sulfonation time is 1 to 10 minutes, and the concentration of the sulfuric acid solution is 95% or higher.
[0025] Further, step 2 includes:
[0026] The first component and the second component are dissolved in a first solvent to obtain a first group of solutions, wherein the first component and / or the second component has a primary amino group;
[0027] The third component is dissolved in the second solvent to obtain the second solution, wherein the third component has functionalized groups;
[0028] The first group of solutions was mixed with the second group of solutions to obtain a mixed solution;
[0029] The mixed solution is present in the reserved area and undergoes a cross-linking reaction, so that the gel fills the microporous structure of the reserved area to form a composite part;
[0030] Preferably, the molar concentration of primary amino groups in the first group of solutions is not greater than the molar concentration of functionalized groups in the second group of solutions;
[0031] More preferably, the molar concentration ratio of primary amino groups in the first group of solutions to functionalized groups in the second group of solutions is 1:(1 to 3.5), preferably 1:(1.2 to 1.4);
[0032] More preferably, the crosslinking reaction takes 0.5 to 2 hours.
[0033] Furthermore, the preparation method of the first component includes the following steps:
[0034] Gelatin and bioactive particles are dissolved in a third solvent to obtain a gelatin-bioactive particle mixed solution;
[0035] The gelatin-bioactive particle mixture solution is cross-linked using a cross-linking agent to obtain a cross-linked product. Preferably, the cross-linking treatment time is 1 to 10 minutes.
[0036] The cross-linked product is pulverized and then freeze-dried to obtain particulate matter, which is the first component.
[0037] Furthermore, in the gelatin-bioactive particle mixed solution, the mass concentration of the bioactive particles is 1% to 20%, and the mass concentration of the gelatin is 5% to 30%; based on the total mass of the gelatin-bioactive particle mixed solution being 100%, the amount of the crosslinking agent added is 0.1% to 5%.
[0038] The present invention also provides a cranioplasty system comprising a cranioplasty implant and a bone adhesive according to the present invention; preferably, the bone adhesive comprises one or more of aldehyde polysaccharides, succinimide polysaccharides, or biodegradable or non-biodegradable cyanoacrylate adhesives.
[0039] The effects of the invention
[0040] The cranial repair implant of the present invention can achieve one-time fixation of inert bone implants, which is convenient to use, can shorten the operation time, and make the bone implantation process quick and convenient.
[0041] The cranioplasty implant of the present invention can reserve a change window for children or patients with changes in bone window, thereby improving the long-term stability of the implant. Furthermore, the cranioplasty implant of the present invention has relatively lower requirements for the edge contour of the bone window, reducing mismatch problems caused by design or manufacturing precision.
[0042] The bioactive particles contained in the cranial repair implant of the present invention can be gradually exposed in the system environment as the gelatin degrades, which helps to induce marginal bone window growth and accelerate bone fusion.
[0043] The method for preparing the cranial repair implant of the present invention is simple and easy to implement, the raw materials are readily available, and it is suitable for mass production.
[0044] The cranioplasty system of the present invention can be directly fixed to the autologous skull without the need for additional fixation components such as cranioplasty locks and fixation nails, thus avoiding damage to intracranial structures. It is more convenient and faster to use and can be used in children or patients with changes in bone windows. Attached Figure Description
[0045] Figure 1 A schematic diagram and a partial enlarged view of the main body, porous region, gel portion, and composite portion of the cranial repair implant of the present invention are shown.
[0046] Figure 2 The image shows a scanning electron microscope (SEM) image of the cranial repair implant of Example 1, wherein the left image is a scanning electron microscope image of the porous region and the right image is a scanning electron microscope image of the composite part;
[0047] Figure 3 The image shows a scanning electron microscope (SEM) image of the cranial repair implant of Example 2, wherein the left image is a scanning electron microscope image of the porous region and the right image is a scanning electron microscope image of the composite part;
[0048] Figure 4 The image shows a scanning electron microscope (SEM) image of the cranial repair implant of Example 3, wherein the left image is a scanning electron microscope image of the porous region and the right image is a scanning electron microscope image of the composite part;
[0049] Figure 5 The image shows a scanning electron microscope (SEM) image of the cranial repair implant of Example 4, wherein the left image is a scanning electron microscope image of the porous region and the right image is a scanning electron microscope image of the composite part;
[0050] Figure 6 The image shows a scanning electron microscope (SEM) image of the cranial repair implant of Example 5, wherein the left image is a scanning electron microscope image of the porous region and the right image is a scanning electron microscope image of the composite part. Detailed Implementation
[0051] Various exemplary embodiments, features, and aspects of the present invention will be described in detail below. The term "exemplary" as used herein means "serving as an example, embodiment, or illustration." Any embodiment described herein as "exemplary" is not necessarily to be construed as superior to or better than other embodiments.
[0052] Furthermore, to better illustrate the present invention, numerous specific details are set forth in the following detailed embodiments. Those skilled in the art should understand that the present invention can be practiced without certain specific details. In other instances, methods, means, apparatus, and steps well known to those skilled in the art have not been described in detail in order to highlight the spirit of the present invention.
[0053] Unless otherwise stated, all units used in this specification are international standard units, and all numerical values and ranges appearing in this invention should be understood to include systematic errors that are unavoidable in industrial production.
[0054] In this specification, the word "may" has two meanings: to perform a certain process and not to perform a certain process.
[0055] In this specification, references to "some specific / preferred embodiments," "other specific / preferred embodiments," "implementation," etc., refer to specific elements (e.g., features, structures, properties, and / or characteristics) related to that embodiment, which are included in at least one of the embodiments described herein and may or may not be present in other embodiments. Furthermore, it should be understood that these elements may be combined in any suitable manner in various embodiments.
[0056] In this specification, the range of values referred to as "value A to value B" refers to the range including the endpoint values A and B.
[0057] In this instruction manual, when "room temperature" or "room temperature" is used, the temperature can be 15-25℃.
[0058] <First Aspect>
[0059] A first aspect of the present invention provides a cranioplasty implant, the cranioplasty implant comprising a main body portion, the main body portion being made of polyaryletherketone, and the main body portion having a through-hole; wherein,
[0060] The area extending within 1 cm from the edge of the main body towards its center is a porous region, which has multiple microporous structures. The gel fills these microporous structures to form a composite portion.
[0061] The gel extends beyond the edge of the main body to form a gel portion.
[0062] The cranioplasty implant of this invention enables one-time fixation of inert bone implants, is convenient to use, shortens surgical time, and makes the bone implantation process quick and convenient. For children or patients with changing bone windows, the cranioplasty implant of this invention can reserve a change window, improving the long-term stability of the implant. Furthermore, the cranioplasty implant of this invention has relatively lower requirements for the contour of the bone window edge, reducing mismatch problems caused by design or manufacturing precision.
[0063] The cranial repair implant of the present invention includes a main body having a through-hole. In the present invention, the diameter of the through-hole is 0.5–5 μm. By providing the through-hole, drainage of accumulated fluid can be facilitated.
[0064] Furthermore, in this invention, the material of the main body comprises polyaryletherketone, preferably comprising one or more combinations of polyetheretherketone, polyetherketone, polyetherketoneketone, polyetheretherketoneketone, and polyetherketoneetherketoneketone.
[0065] The area extending within 1 cm, preferably 0.1 to 1 cm, from the edge of the main body towards its center is a porous region. This porous region has multiple microporous structures, allowing the gel to fill these microporous structures and form a composite portion. Since the composite portion exists in the edge region of the cranial bone repair implant, and the gel of this invention is biodegradable, bone tissue can grow into the microporous structures after the gel in the composite portion degrades.
[0066] In some specific implementations, the average pore size of the microporous structure is 0.5–5 μm, and the area of the upper surface of the porous region is 10%–70% of the upper surface area of the main body. When the average pore size of the microporous structure is 0.5–5 μm, and the area of the upper surface of the porous region is 10%–70% of the upper surface area of the main body, the obtained cranial repair implant exhibits excellent adhesion and static compressive strength.
[0067] Furthermore, the gel extends beyond the edge of the main body to form a gel portion. Specifically, the distance the gel extends beyond the edge of the main body is within 1 cm, preferably 0.1 to 1 cm. Because the cranioplasty implant of the present invention has a gel portion, for areas with mismatched dimensions, the cranioplasty implant can be adapted to the defective bone window by trimming the gel portion. The gel portion between the edge of the cranioplasty implant of the present invention and the contact point with the bone window is a gel with a certain degree of elasticity and toughness, thus possessing a certain supporting strength, but can also be trimmed by cutting.
[0068] In some specific embodiments, the raw materials of the gel include a first component, a second component, and a third component; wherein the first component includes gelatin-encapsulated bioactive particles, the second component includes biodegradable materials with primary amino groups, and the third component includes polysaccharides with functionalized groups.
[0069] A dual-network hydrogel structure is formed by cross-linking the first component, the second component, and the third component of the present invention. The dual-network hydrogel structure includes: a first network structure formed by the reaction of the first component and the third component, and a second network structure formed by the reaction of the second component and the third component.
[0070] In some specific embodiments, the present invention uses gelatin-coated bioactive particles as a first component, such that the surface of the first component contains primary amino and / or carboxyl groups. The inventors of the present invention have found that using gelatin-coated bioactive particles allows the bioactive particles to be gradually exposed in the system environment as the gelatin degrades, which helps to induce marginal bone window growth or accelerate bone fusion. If the bioactive particles are directly filled into the microporous structure of the main body, the bioactive particles may settle, thus affecting the uniformity of the composite; therefore, the present invention preferably encapsulates the bioactive particles.
[0071] Preferably, in this invention, the bioactive particles have a particle size of 0.1 to 3.0 μm, which can be prepared by grinding or physically pulverizing to the target size.
[0072] Bioactive particles can be commercially available or prepared using existing technologies. Specifically, the bioactive particles include one or more of the following: bioactive glass materials, biodegradable metals, biodegradable metal oxides, biodegradable metal salts, hydroxyapatite, tricalcium phosphate, biodegradable metal alloys, and recombinant human bone morphogenetic proteins. The biodegradable metal can be magnesium or zinc; the biodegradable metal salt can be a biodegradable metal chloride, such as zinc chloride or magnesium oxide.
[0073] In some specific embodiments, the present invention uses a biodegradable material having primary amino groups as a second component. In the biodegradable material having primary amino groups, each repeating unit of the biodegradable material contains two or more primary amino functional groups. Preferably, the second component comprises one or a combination of two or more of gelatin, polyethyleneimine, or polylysine. More preferably, the gelatin has a relative molecular weight of 10,000 to 100,000 g / mol and contains more than 50 primary amino functional groups; the polyethyleneimine has a relative molecular weight of 1,000 to 3,000 g / mol and contains more than 15 primary amino functional groups; the polylysine has a relative molecular weight of 2,000 to 5,000 g / mol and contains more than 27 primary amino functional groups.
[0074] Since the primary amino content of the first component is low and its cross-linking efficiency with the third component is not high, the present invention uses the second component to further react with the third component to form a second network structure, which is beneficial to enhance and stabilize the first network structure formed by the reaction of the first component and the third component.
[0075] In some specific embodiments, the third component comprises a polysaccharide having functionalized groups. In the polysaccharide with functionalized groups, each repeating unit of the polysaccharide has at least two functionalized groups. Preferably, the relative molecular weight of the polysaccharide is 1000–10000 g / mol. Preferably, the functionalized groups include aldehyde groups and / or succinimide groups.
[0076] By using the third component, a stable double-network hydrogel structure can be formed by reacting with the primary amino groups of the first and second components.
[0077] The gel raw materials used in this invention can be purchased directly or synthesized in-house. Aldehyde-modified polysaccharides can be prepared by oxidizing polysaccharides with sodium periodate, or aldehyde-modified hyaluronic acid can be purchased directly. Alternatively, succinimide-modified polysaccharides, such as succinimide-modified hyaluronic acid, can also be purchased directly.
[0078] In some specific implementations, the mass ratio of the first component to the sum of the second and third components is (3–7):(10–20); and the mass ratio of the second component to the third component is (0.8–2):1. When the mass ratio of the first component to the sum of the second and third components is (3–7):(10–20); and the mass ratio of the second component to the third component is (0.8–2):1, it is easier to obtain the desired dual-network hydrogel structure.
[0079] Specifically, the mass ratio of the second to the third component may vary depending on the raw materials used. For example, when polyethyleneimine is used as the second component, the mass ratio of the second to the third component is 0.8–1.2:1; when polylysine is used as the second component, the mass ratio is 1.0–1.4:1; and when gelatin is used as the second component, the mass ratio is 1.5–2.0:1. Meeting these ratios results in a gel with low swelling behavior.
[0080] <Second aspect>
[0081] A second aspect of the present invention provides a method for preparing a cranioplasty implant according to the first aspect of the present invention, comprising the following steps:
[0082] Step 1: A reserved area is formed within 1 cm from the edge of the skull repair matrix containing polyaryletherketone material to the center, and the reserved area of the matrix is pretreated to form a microporous structure to obtain a pretreated product.
[0083] Step 2: Fill the microporous structure of the reserved area with gel to form a composite part;
[0084] Step 3: Extend the gel beyond the edge of the substrate to form a gel portion, thereby obtaining a cranial repair implant.
[0085] The method for preparing the cranial repair implant of the present invention is simple and easy to implement, the raw materials are readily available, and it is suitable for mass production.
[0086] The substrate can be purchased or prepared using existing technologies. This invention uses a substrate to form the main body of the cranioplasty implant. Specifically, based on information about the cranioplasty defect, a substrate for the cranioplasty implant, comprising polyaryletherketone (PATK), can be prepared using personalized design and machining to match its contour and arc height structure. A reserved area is formed within 1 cm from the edge of the substrate towards the center, based on design requirements. The substrate for the cranioplasty implant is then manufactured using 3D printing or machining.
[0087] For 3D printing, micropores with an average pore size of 0.5–5.0 μm are directly formed in the reserved area, resulting in a porous skull repair implant matrix. For machining, the implant matrix can be machined using a suitable cutting tool to create pores in the reserved area, resulting in micropores with an average pore size of 0.5–5.0 μm. The area of the porous region's upper surface is 10%–70% of the upper surface area of the matrix.
[0088] In this invention, the pretreatment includes the steps of sulfonation and / or plasma treatment of the reserved area of the substrate.
[0089] For sulfonation treatment, specifically, the reserved area of the cranioplasty implant matrix can be sulfonated using a sulfuric acid solution with a concentration of 95% or higher. Specifically, the cranioplasty implant matrix is placed flat in a container, ensuring the reserved area is completely submerged in the sulfuric acid solution. The size of the reserved area is less than 1 cm, for example, 0.1–1 cm. The reserved area is sulfonated under magnetic stirring or ultrasonic conditions for 1–10 minutes.
[0090] After sulfonation, the matrix is removed from the sulfuric acid solution and washed with acid-base neutralization or plenty of water to ensure that no acidic substances remain on the outer surface and pore surfaces of the matrix. After sulfonation, a three-dimensional network structure appears in the reserved areas of the matrix, and sulfonic acid groups are formed on the matrix surface, which improves the material's biocompatibility and provides some antibacterial properties. Furthermore, in this invention, sulfonation can further reduce the pore size of the microporous structure, increase porosity, and enhance the hydrophilicity of the reserved areas.
[0091] Furthermore, after sulfonation, the sulfuric acid residue can be removed by alternating rinsing, sonication, and soaking with water and / or a low-molar-concentration alkaline solution (e.g., a sodium hydroxide solution with a molar concentration of 0.01–0.5 mol / L). Finally, the solution is thoroughly rinsed with water and dried for later use.
[0092] For plasma treatment, the chemical inertness of the matrix material, polyaryletherketone, necessitates surface physical modification. Plasma immersion ion implantation and deposition techniques can introduce various elements or chemical functional groups onto the matrix surface, enabling the regulation of the matrix's mechanical properties, bioactivity, and antibacterial properties. Furthermore, water vapor plasma immersion ion implantation can form hydroxyl functional groups on the material surface, thereby enhancing the matrix's bioactivity.
[0093] The pretreated reserved area develops more microporous structures and increases hydrophilicity, thereby enhancing the binding ability of the gel to the microporous structures. The pretreated reserved area can then be composited with the gel to form an adhesive composite structure.
[0094] In some specific implementations, step 2 of the present invention includes:
[0095] The first component and the second component are dissolved in a first solvent to obtain a first solution, wherein the first component and / or the second component has a primary amino group;
[0096] The third component is dissolved in the second solvent to obtain the second solution, wherein the third component has functionalized groups;
[0097] The first group of solutions was mixed with the second group of solutions to obtain a mixed solution;
[0098] The mixed solution is present in the reserved area and undergoes a cross-linking reaction, so that the gel fills the microporous structure of the reserved area to form a composite part.
[0099] Specifically, the molar concentration of primary amino groups in the first group of solutions is not greater than the molar concentration of functionalized groups in the second group of solutions. By ensuring that the molar concentration of primary amino groups is not greater than the molar concentration of functionalized groups, the cross-linking reaction can proceed effectively.
[0100] More preferably, the molar concentration ratio of primary amino groups in the first group of solutions to functionalized groups in the second group of solutions is 1:(1 to 3.5), preferably 1:(1.2 to 1.4). When the molar concentration ratio of primary amino groups in the first group of solutions to functionalized groups in the second group of solutions is 1:(1 to 3.5), the degree of crosslinking is more suitable, and a hydrogel with low swelling or even almost no swelling can be formed.
[0101] Specifically, the concentration of solute in the mixed solution is 10% to 25%, preferably 18% to 22%; when the concentration of solute in the mixed solution is 10% to 25%, cross-linking can be completed more effectively.
[0102] Specifically, the cross-linking reaction takes 0.5 to 2 hours. When the cross-linking reaction takes 0.5 to 2 hours, the cross-linking reaction can be completed more effectively.
[0103] In addition, since the polysaccharide in the third component still contains unreacted functional groups, such as aldehydes or succinimides, these functional groups can react with amino groups on the surface of surrounding tissues, which is beneficial for further fixation between the cranial repair implant and the autologous skull.
[0104] Specifically, after obtaining the mixed solution, the reserved area of the pretreated product can be immediately immersed in the mixed solution. The solution is then used to completely saturate the reserved area using methods such as vibration and ultrasound, and a curing and cross-linking reaction is carried out in the reserved area. After the curing and cross-linking reaction, the gel is trimmed along the edge contour structure to ensure a smooth connection between the overall contour structure of the gel portion and the composite portion, and to allow for a tight connection with the autologous bone window. Preferably, the distance the gel extends beyond the edge of the substrate is within 1 cm to form the gel portion.
[0105] Furthermore, the mixed solution can be drop-coated onto the reserved area, and locally it can be combined with the edge microporous structure by extrusion to obtain a composite layer. The distance from the edge of the substrate to the center of the substrate and the distance from the gel to the edge of the substrate can be controlled based on the extrusion amount. If necessary, external force, such as pressure, can be used to form the composite part and the gel part.
[0106] In some specific implementations, the preparation method of the first component includes the following steps:
[0107] Gelatin and bioactive particles are dispersed in a third solvent to obtain a gelatin-bioactive particle mixed solution;
[0108] The gelatin-bioactive particle mixture solution was cross-linked using a cross-linking agent to obtain a cross-linked product;
[0109] The cross-linked product is pulverized and then freeze-dried to obtain particulate matter, which is the first component.
[0110] In some specific embodiments, the mass concentration of the bioactive particles in the gelatin-bioactive particle mixed solution is 1% to 20%, and the mass concentration of the gelatin is 5% to 30%.
[0111] Specifically, gelatin can first be dissolved in a third solvent to obtain a gelatin solution; then, bioactive particles can be dispersed in the gelatin solution to obtain a gelatin-bioactive particle mixed solution. Further, gelatin is dispersed in a purified aqueous solution, heated to 35℃~40℃, and continuously mechanically stirred until the gelatin is completely dissolved. Then, bioactive particles are added, and stirring is continued to disperse the bioactive particles in the solution system.
[0112] After the gelatin-bioactive particle mixture has stabilized for 5-15 minutes, a crosslinking agent solution is slowly added dropwise. The gelatin will gradually crosslink and solidify into a gel. Once a gel has formed, the stirring speed is reduced, and stirring is stopped when the gelatin solution becomes noticeably viscous. Based on the total mass of the gelatin-bioactive particle mixture (100%), the amount of crosslinking agent added is 0.1%-5%. Specifically, the mass concentration of the crosslinking agent in the crosslinking agent solution can be 1-30%.
[0113] Furthermore, in this invention, the crosslinking treatment time is 1–10 min. Through the crosslinking treatment, the desired crosslinked product can be obtained, which is essentially gelatin encapsulating bioactive particles. The crosslinking agent is not particularly limited in this invention and can be a commonly used crosslinking agent in the art, such as genipin and / or carbodiimide compounds, such as 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDC), etc.
[0114] The cross-linked product is then pulverized and freeze-dried to obtain particulate matter, which is gelatin-encapsulated bioactive particles. The cross-linked product can be physically pulverized and washed with a polar solvent to remove the cross-linking agent, unencapsulated bioactive particles, and / or uncross-linked gelatin. Specifically, the polar solvent can be an alcohol solvent and / or water; preferably, a 50%–80% alcohol solvent is used for washing. Due to the presence of gelatin, the surface of the first component contains primary amino and / or carboxyl groups.
[0115] <Third aspect>
[0116] A third aspect of the present invention also provides a cranioplasty system, comprising the aforementioned cranioplasty implant and a bone adhesive, wherein the bone adhesive is an aldehyde-modified polysaccharide, a succinimide-modified polysaccharide, or a biodegradable or non-biodegradable cyanoacrylate adhesive. After the edge contour structure of the aforementioned cranioplasty implant is adapted to the autologous skull, the addition of bone adhesive can make the cranioplasty implant adhere more firmly and tightly to the autologous skull and surrounding soft tissues, thereby further enhancing the fixation effect of the implant.
[0117] Example
[0118] The embodiments of the present invention will be described in detail below with reference to examples. However, those skilled in the art will understand that the following examples are for illustrative purposes only and should not be considered as limiting the scope of the invention. Unless otherwise specified in the examples, conventional conditions or conditions recommended by the manufacturer are followed. Reagents or instruments whose manufacturers are not specified are all commercially available conventional products.
[0119] Example 1
[0120] 1. A polyetheretherketone (PEEK) elliptical prosthesis (60mm × 50mm, circumference 35.4cm) with matching contour and arc height structure is prepared by machining to be used as the substrate. Based on the design requirements, a 0.2cm long reserve is made at the position where the entire edge of the PEEK elliptical prosthesis extends towards the center, forming a reserved area.
[0121] 2. The reserved area of the PEEK elliptical prosthesis was immersed in a 98% concentrated sulfuric acid solution and sonicated for 6 minutes. After removal, it was alternately rinsed, sonicated, and soaked with purified water and 0.1 mol / L sodium hydroxide solution to remove sulfuric acid residue. Finally, it was thoroughly rinsed with purified water and dried for later use, forming a porous region with multiple microporous structures. Optical microscopy showed that the average pore size of the microporous structure was 2.5 μm. The surface area of the porous region was approximately 40% of the surface area of the substrate, thus obtaining the pretreated prosthesis.
[0122] 3. Measure 5g of bioactive glass particles with a particle size of approximately 1μm (after grinding and sieving), and 15g of gelatin particles. Disperse them together in 95ml of purified aqueous solution. Heat to 37℃ and stir mechanically until the gelatin is completely dissolved and the solution is in an emulsion state, to obtain a gelatin-bioactive glass particle mixed solution. Separately, measure 2g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDC) and disperse it in 5ml of purified water. After complete dissolution, obtain an EDC solution. Add the EDC solution dropwise to the gelatin-bioactive glass particle mixed solution and stop the reaction after 5min. At this time, the solution is in a continuous gel state, to obtain the cross-linked product.
[0123] 4. Place the cross-linked product obtained in step 3 into 1000 ml of purified aqueous solution. After full swelling, perform physical cutting and pulverization. After pulverization, soak the product three times with 75% alcohol and centrifuge to settle it. Then freeze-dry it and perform physical pulverization twice. After sieving, retain particles with a particle size of 1.5-2.5 μm, which is the first component, for later use.
[0124] 5. Weigh 1g of the first component obtained in step 4 and dissolve it together with 3g of freshly weighed gelatin in 10ml of purified water to obtain the first solution; separately, weigh 1.5g of succinimide polysaccharide and dissolve it in 10ml of purified water to obtain the second solution. Place the reserved area of the pre-treated prosthesis obtained in step 2 flat in a wide-mouthed container. Pour the mixture of the first and second solutions into the wide-mouthed container and cover the reserved area of the pre-treated prosthesis to form a reaction system. Place the above reaction system in an ultrasonic oscillation to accelerate the solution wetting and cross-linking reaction, and stop the reaction after 1 hour. Remove excess material along the edge contour of the pre-treated prosthesis, so that the cross-linked gel fills the microporous structure of the reserved area to form a composite part, and the cross-linked gel extends 0.2cm outward from the edge of the pre-treated prosthesis to form a gel part, thus obtaining the cranioplasty implant.
[0125] 6. The skull repair implant obtained in step 5 is subjected to irradiation sterilization to ensure a sterile state, thus obtaining the skull repair implant product.
[0126] Example 2
[0127] 1. Based on the information of the pig skull defect, a polyetheretherketone (PEEK) elliptical prosthesis (60mm×50mm, circumference 35.4cm) with a matched contour and arc height structure was prepared by personalized design and additive manufacturing as the substrate. Based on the design requirements, a 0.4cm long reserve was made along the entire edge of the PEEK elliptical prosthesis extending towards the center, forming a reserved area.
[0128] 2. The reserved area of the PEEK elliptical prosthesis was immersed in a 98% concentrated sulfuric acid solution, sonicated for 3 minutes, and then removed. It was then rinsed, sonicated, and soaked alternately with purified water and 0.1 mol / L sodium hydroxide solution to remove sulfuric acid residue. Finally, it was thoroughly rinsed with purified water and dried for later use, forming a porous region with multiple microporous structures. Optical microscopy showed that the average pore size of the microporous structure was 1 μm. The area of the upper surface of the porous region was approximately 20% of the upper surface area of the substrate, thus obtaining the pretreated prosthesis.
[0129] 3. Measure 3g of bioactive glass particles with a particle size of approximately 0.3μm (after grinding and sieving), and 10g of gelatin particles. Disperse them together in 45ml of purified aqueous solution. Heat to 37℃ and stir mechanically until the gelatin is completely dissolved and the solution is in an emulsion state to obtain a gelatin-bioactive glass particle mixed solution. Separately, measure 0.5g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDC) and disperse it in 5ml of purified water. After complete dissolution, obtain an EDC solution. Add the EDC solution dropwise to the gelatin-bioactive glass particle mixed solution and stop the reaction after 5min. At this time, the solution is in a continuous gel state, and the cross-linked product is obtained.
[0130] 4. Place the cross-linked product obtained in step 3 into 200 ml of purified aqueous solution. After full swelling, perform physical cutting and pulverization. After pulverization, soak the product three times with 75% alcohol and centrifuge to settle it. Then freeze-dry the product and perform physical pulverization twice. After sieving, retain particles with a particle size of 0.3 to 0.7 μm, which is the first component, for later use.
[0131] 5. Weigh 1.6g of the first component obtained in step 4 and dissolve it together with 6.5g of freshly weighed gelatin in 20ml of purified water to obtain the first solution; separately, weigh 4g of succinimide polysaccharide and dissolve it in 50ml of purified water to obtain the second solution. Place the reserved area of the pre-treated prosthesis obtained in step 2 flat in a wide-mouthed container. Pour the mixture of the first and second solutions into the wide-mouthed container and cover the reserved area of the pre-treated prosthesis to form a reaction system. Place the above reaction system in an ultrasonic oscillation to accelerate the solution wetting and cross-linking reaction, and stop the reaction after 1 hour. Remove excess material along the edge contour of the pre-treated prosthesis so that the cross-linked gel fills the microporous structure of the reserved area to form a composite part. Furthermore, the cross-linked gel extends 0.4cm outward from the edge of the pre-treated prosthesis to form a gel part, thus obtaining the cranioplasty implant.
[0132] 6. The skull repair implant obtained in step 5 is subjected to irradiation sterilization to ensure a sterile state, thus obtaining the skull repair implant product.
[0133] Example 3
[0134] 1. Based on the information of the pig skull defect, a PEEK elliptical prosthesis (60mm×50mm, circumference 35.4cm) with matching contour and arc height structure was mechanically prepared as the base. Based on the design requirements, a 0.8cm long reserve was made at the position where the entire edge of the PEEK elliptical prosthesis extends towards the center, forming a reserved area.
[0135] 2. The reserved area of the PEEK elliptical prosthesis was immersed in a 98% concentrated sulfuric acid solution, sonicated for 10 minutes, and then removed. It was then rinsed, sonicated, and soaked alternately with purified water and 0.1 mol / L sodium hydroxide solution to remove sulfuric acid residue. Finally, it was thoroughly rinsed with purified water and dried for later use, forming a porous region with multiple microporous structures. Optical microscopy showed that the average pore size of the microporous structure was approximately 3 μm. The surface area of the porous region was approximately 70% of the surface area of the substrate, thus obtaining the pretreated prosthesis.
[0136] 3. Measure 5g of bioactive glass particles with a particle size of approximately 2μm (after grinding and sieving), and 30g of gelatin particles. Disperse them together in 90ml of purified aqueous solution. Heat to 37℃ and stir mechanically until the gelatin is completely dissolved and the solution is in an emulsion state, to obtain a gelatin-bioactive glass particle mixed solution. Separately, measure 3g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDC) and disperse it in 10ml of purified water. After complete dissolution, obtain an EDC solution. Add the EDC solution dropwise to the gelatin-bioactive glass particle mixed solution and stop the reaction after 5min. At this time, the solution is in a continuous gel state, to obtain the cross-linked product.
[0137] 4. Place the cross-linked product obtained in step 3 into 1000 ml of purified aqueous solution. After full swelling, perform physical cutting and pulverization. After pulverization, soak the product three times with 75% alcohol and centrifuge to settle it. Then freeze-dry it and perform physical pulverization twice. After sieving, retain particles with a particle size of 2-4 μm, which is the first component, for later use.
[0138] 5. Weigh 2g of the first component obtained in step 4, and separately measure 8g of gelatin. Dissolve them together in 75ml of purified water to obtain the first solution. Separately measure 5g of aldehyde-modified polysaccharide and dissolve it in 60ml of purified water to obtain the second solution. Place the reserved area of the pre-treated prosthesis obtained in step 2 flat in a wide-mouthed container. Pour the mixture of the first and second solutions into the wide-mouthed container and cover the reserved area of the pre-treated prosthesis to form a reaction system. Place the above reaction system in an ultrasonic oscillation to accelerate the solution wetting and cross-linking reaction. Stop the reaction after 1 hour. Remove excess material along the edge contour of the pre-treated prosthesis, allowing the cross-linked gel to fill the microporous structure of the reserved area to form a composite part. Furthermore, the cross-linked gel extends 0.5cm outward from the edge of the pre-treated prosthesis to form a gel part, obtaining the cranioplasty implant.
[0139] 6. The skull repair implant obtained in step 5 is subjected to irradiation sterilization to ensure a sterile state, thus obtaining the skull repair implant product.
[0140] Example 4
[0141] 1. Based on the design information of the pig skull defect, a polyetheretherketone (PEEK) elliptical prosthesis (60mm×50mm, circumference 35.4cm) with matching contour and arc height structure was mechanically prepared as the substrate. Based on the design requirements, a 0.8cm long reserve was made along the entire edge of the PEEK elliptical prosthesis extending towards the center, forming a reserved area.
[0142] 2. The reserved area of the PEEK elliptical prosthesis was immersed in a 98% concentrated sulfuric acid solution, sonicated for 10 minutes, and then removed. It was then rinsed, sonicated, and soaked alternately with purified water and 0.1 mol / L sodium hydroxide solution to remove sulfuric acid residue. Finally, it was thoroughly rinsed with purified water and dried for later use, forming a porous region with multiple microporous structures. Optical microscopy showed that the average pore size of the microporous structure was approximately 3 μm. The surface area of the porous region was approximately 70% of the surface area of the substrate, thus obtaining the pretreated prosthesis.
[0143] 3. Measure 5g of bioactive glass particles with a particle size of approximately 2μm (after grinding and sieving), and 30g of gelatin particles. Disperse them together in 90ml of purified aqueous solution. Heat to 37℃ and stir mechanically until the gelatin is completely dissolved and the solution is in an emulsion state to obtain a gelatin-bioactive glass particle mixed solution. Separately, measure 3g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDC) and disperse it in 10ml of purified water. After complete dissolution, obtain an EDC solution. Add the EDC solution dropwise to the gelatin-bioactive glass particle mixed solution and stop the reaction after 5min. At this time, the solution is in a continuous gel state, and the cross-linked product is obtained.
[0144] 4. Place the cross-linked product obtained in step 3 into 1000 ml of purified aqueous solution. After full swelling, perform physical cutting and pulverization. After pulverization, soak the product three times with 75% alcohol and centrifuge to settle it. Then freeze-dry it and perform physical pulverization twice. After sieving, retain particles with a particle size of 2 μm to 4 μm, which is the first component, for later use.
[0145] 5. Weigh 2g of the first component obtained in step 4, and separately measure 4g of polyethyleneimine (PEI). Dissolve both in 20ml of purified water to obtain the first solution. Separately measure 5g of aldehyde-modified polysaccharide and dissolve in 60ml of purified water to obtain the second solution. Place the reserved area of the pre-treated prosthesis obtained in step 2 flat in a wide-mouthed container. Pour the mixture of the first and second solutions into the wide-mouthed container and cover the reserved area of the pre-treated prosthesis to form a reaction system. Place the reaction system in an ultrasonic oscillation chamber to accelerate the solution wetting and cross-linking reaction. Stop the reaction after 1 hour. Remove excess material along the edge contour of the pre-treated prosthesis, allowing the cross-linked gel to fill the microporous structure of the reserved area to form a composite part. The cross-linked gel extends 0.5cm outward from the edge of the pre-treated prosthesis to form a gel part, thus obtaining the cranioplasty implant.
[0146] 6. The skull repair implant obtained in step 5 is subjected to irradiation sterilization to ensure a sterile state, thus obtaining the skull repair implant product.
[0147] Example 5
[0148] 1. Based on the design information of the pig skull defect, a polyetheretherketone (PEEK) elliptical prosthesis (60mm×50mm, circumference 35.4cm) with matching contour and arc height structure was mechanically prepared as the substrate. Based on the design requirements, a 0.8cm long reserve was made along the entire edge of the PEEK elliptical prosthesis extending towards the center, forming a reserved area.
[0149] 2. The reserved area of the PEEK elliptical prosthesis was immersed in a 98% concentrated sulfuric acid solution, sonicated for 10 minutes, and then removed. It was then rinsed, sonicated, and soaked alternately with purified water and 0.1 mol / L sodium hydroxide solution to remove sulfuric acid residue. Finally, it was thoroughly rinsed with purified water and dried for later use, forming a porous region with multiple microporous structures. Optical microscopy showed that the average pore size of the microporous structure was approximately 3 μm. The surface area of the porous region was approximately 70% of the surface area of the substrate, thus obtaining the pretreated prosthesis.
[0150] 3. Measure 5g of bioactive glass particles with a particle size of approximately 2μm (after grinding and sieving), and 30g of gelatin particles. Disperse them together in 90ml of purified aqueous solution. Heat to 37℃ and stir mechanically until the gelatin is completely dissolved and the solution is in an emulsion state, to obtain a gelatin-bioactive glass particle mixed solution. Separately, measure 3g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDC) and disperse it in 10ml of purified water. After complete dissolution, obtain an EDC solution. Add the EDC solution dropwise to the gelatin-bioactive glass particle mixed solution and stop the reaction after 5min. At this time, the solution is in a continuous gel state, to obtain the cross-linked product.
[0151] 4. Place the cross-linked product obtained in step 3 into 1000 ml of purified aqueous solution. After full swelling, perform physical cutting and pulverization. After pulverization, soak the product three times with 75% alcohol and centrifuge to settle it. Then freeze-dry it and perform physical pulverization twice. After sieving, retain particles with a particle size of 2-4 μm, which is the first component, for later use.
[0152] 5. Weigh 2g of the first component obtained in step 4, and separately weigh 6g of polylysine (Ply), and dissolve them together in 30ml of phosphate buffer solution (pH=10) to obtain the first solution group; separately weigh 5g of succinimide polysaccharide and dissolve it in 60ml of purified water to obtain the second solution group. Place the reserved area of the pre-treated prosthesis obtained in step 2 flat in a wide-mouthed container, pour the mixture of the first and second solutions into the wide-mouthed container and cover the reserved area of the pre-treated prosthesis to form a reaction system. Place the above reaction system in an ultrasonic oscillation to accelerate the solution wetting and cross-linking reaction, and stop the reaction after 1 hour. Remove excess material along the edge contour of the pre-treated prosthesis, so that the cross-linked gel fills the microporous structure of the reserved area to form a composite part. Furthermore, the cross-linked gel extends 0.5cm outward from the edge of the pre-treated prosthesis to form a gel part, thus obtaining the cranioplasty implant.
[0153] 6. The skull repair implant obtained in step 5 is subjected to irradiation sterilization to ensure a sterile state, thus obtaining the skull repair implant product.
[0154] Comparative Example 1
[0155] 1. Based on the design information of the pig skull defect, a polyetheretherketone (PEEK) elliptical prosthesis (60mm×50mm, circumference 35.4cm) with matching contour and arc height structure was mechanically prepared as the substrate. Based on the design requirements, a 0.8cm long reserve was made along the entire edge of the PEEK elliptical prosthesis extending towards the center, forming a reserved area.
[0156] 2. The reserved area of the PEEK elliptical prosthesis was immersed in a 98% concentrated sulfuric acid solution and sonicated for 10 minutes. After removal, it was alternately rinsed, sonicated, and soaked in a 0.1 mol / L sodium hydroxide solution of purified water to remove sulfuric acid residue. Finally, it was thoroughly rinsed with purified water and dried for later use, forming a porous region with multiple microporous structures. Optical microscopy showed that the average pore size of the microporous structure was approximately 3 μm. The surface area of the porous region was approximately 70% of the surface area of the substrate, thus obtaining the pretreated prosthesis.
[0157] 3. Measure 5g of bioactive glass particles with a particle size of approximately 2μm (after grinding and sieving), and 30g of gelatin particles. Disperse them together in 90ml of purified aqueous solution. Heat to 37℃ and stir mechanically until the gelatin is completely dissolved and the solution is in an emulsion state, to obtain a gelatin-bioactive glass particle mixed solution. Separately, measure 3g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDC) and disperse it in 10ml of purified water. After complete dissolution, obtain an EDC solution. Add the EDC solution dropwise to the gelatin-bioactive glass particle mixed solution and stop the reaction after 5min. At this time, the solution is in a continuous gel state, to obtain the cross-linked product.
[0158] 4. Place the cross-linked product obtained in step 3 into 1000 ml of purified aqueous solution. After full swelling, perform physical cutting and pulverization. After pulverization, soak the product three times with 75% alcohol and centrifuge to settle it. Then freeze-dry it and perform physical pulverization twice. After sieving, retain particles with a particle size of 2-4 μm, which is the first component, for later use.
[0159] 5. Weigh 2g of the first component obtained in step 4, and separately measure 11g of gelatin. Dissolve them together in 110ml of purified water to obtain the first solution. Separately measure 5g of succinimide polysaccharide and dissolve it in 60ml of purified water to obtain the second solution. Place the reserved area of the pre-treated prosthesis obtained in step 2 flat in a wide-mouthed container. Pour the mixture of the first and second solutions into the wide-mouthed container and cover the reserved area of the pre-treated prosthesis to form a reaction system. Place the above reaction system in an ultrasonic oscillation to accelerate the solution wetting and cross-linking reaction. Stop the reaction after 1 hour. Remove excess material along the edge contour of the pre-treated prosthesis, allowing the cross-linked gel to fill the microporous structure of the reserved area to form a composite part. Furthermore, the cross-linked gel extends 0.5cm outward from the edge of the pre-treated prosthesis to form a gel part, obtaining the cranioplasty implant.
[0160] 6. The skull repair implant obtained in step 5 is subjected to irradiation sterilization to ensure a sterile state, thus obtaining the skull repair implant product;
[0161] Comparative Example 2
[0162] 1. Based on the information of the pig skull defect, a PEEK elliptical prosthesis (60mm×50mm, circumference 35.4cm) with matching contour and arc height structure was mechanically prepared as the base. Based on the design requirements, a 0.2cm long reserve was made at the position where the entire edge of the PEEK elliptical prosthesis extends towards the center, forming a reserved area.
[0163] 2. The reserved area of the PEEK elliptical prosthesis was immersed in a 98% concentrated sulfuric acid solution and sonicated for 6 minutes. After removal, it was alternately rinsed, sonicated, and soaked with purified water and 0.1 mol / L sodium hydroxide solution to remove sulfuric acid residue. Finally, it was thoroughly rinsed with purified water and dried for later use, forming a porous region with multiple microporous structures. Optical microscopy showed that the average pore size of the microporous structure was approximately 2.5 μm. The surface area of the porous region was approximately 40% of the surface area of the substrate, thus obtaining the pretreated prosthesis.
[0164] 3. Measure 5g of bioactive glass particles with a particle size of approximately 1μm (after grinding and sieving), and 15g of gelatin particles, disperse them in 95ml of purified aqueous solution, heat to 37℃, and use mechanical stirring until the gelatin is completely dissolved and the solution is in an emulsion state to obtain a gelatin-bioactive glass particle mixed solution; separately measure 2g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDC) and disperse it in 5ml of purified water. After complete dissolution, an EDC solution is obtained. Add the EDC solution dropwise to the gelatin-bioactive glass particle mixed solution, and stop the reaction after 5min. At this time, the solution is in a continuous gel state, and the cross-linked product is obtained.
[0165] 4. Place the cross-linked product obtained in step 3 into 1000 ml of purified aqueous solution. After full swelling, perform physical cutting and pulverization. After pulverization, soak the product three times with 75% alcohol and centrifuge to settle it. Then freeze-dry it and perform physical pulverization twice. After sieving, retain particles with a particle size of 1.5-2.5 μm, which is the first component, for later use.
[0166] 5. Weigh 1g of the first component obtained in step 4, and separately measure 0.25g of polyethyleneimine (PEI). Dissolve both in 20ml of purified water to obtain the first solution. Separately measure 1.5g of aldehyde-modified polysaccharide and dissolve in 10ml of purified water to obtain the second solution. Place the reserved area of the pre-treated prosthesis obtained in step 2 flat in a wide-mouthed container. Pour the mixture of the first and second solutions into the wide-mouthed container and cover the reserved area of the pre-treated prosthesis to form a reaction system. Place the reaction system in an ultrasonic oscillation chamber to accelerate the solution wetting and cross-linking reaction. Stop the reaction after 1 hour. Remove excess material along the edge contour of the pre-treated prosthesis, allowing the cross-linked gel to fill the microporous structure of the reserved area to form a composite part. The cross-linked gel extends 0.2cm outward from the edge of the pre-treated prosthesis to form a gel part, thus obtaining the cranioplasty implant.
[0167] 6. The skull repair implant obtained in step 5 is subjected to irradiation sterilization to ensure a sterile state, thus obtaining the skull repair implant product.
[0168] Comparative Example 3
[0169] 1. Based on the information of the pig skull defect, a PEEK elliptical prosthesis (60mm×50mm, circumference 35.4cm) with matching contour and arc height structure was mechanically prepared as the base. Based on the design requirements, a 0.8cm extension was made from the edge of the PEEK elliptical prosthesis towards the center, forming a reserved area.
[0170] 2. The reserved area of the PEEK elliptical prosthesis was immersed in a 98% concentrated sulfuric acid solution and sonicated for 15 minutes. After removal, it was alternately rinsed, sonicated, and soaked with purified water and 0.1 mol / L sodium hydroxide solution to remove sulfuric acid residue. Finally, it was thoroughly rinsed with purified water and dried for later use, forming a porous region with multiple microporous structures. Optical microscopy showed that the average pore size of the microporous structure was 5 μm. The surface area of the porous region was approximately 80% of the surface area of the substrate, thus obtaining the pretreated prosthesis.
[0171] 3. Measure 5g of bioactive glass particles with a particle size of approximately 2μm (after grinding and sieving), and 30g of gelatin particles. Disperse them together in 90ml of purified aqueous solution. Heat to 37℃ and stir mechanically until the gelatin is completely dissolved and the solution is in an emulsion state, to obtain a gelatin-bioactive glass particle mixed solution. Separately, measure 3g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDC) and disperse it in 10ml of purified water. After complete dissolution, obtain an EDC solution. Add the EDC solution dropwise to the gelatin-bioactive glass particle mixed solution. Stop the reaction after 5min. At this time, the solution is in a continuous gel state, to obtain the cross-linked product.
[0172] 4. Place the cross-linked product obtained in step 3 into 1000 ml of purified aqueous solution. After full swelling, perform physical cutting and pulverization. After pulverization, soak the product three times with 75% alcohol and centrifuge to settle it. Then freeze-dry it and perform physical pulverization twice. After sieving, retain particles with a particle size of 2 μm to 4 μm, which is the first component, for later use.
[0173] 5. Weigh 2g of the first component obtained in step 4, and separately measure 6g of polylysine (Ply). Dissolve both in 30ml of phosphate buffer solution (pH=10) to obtain the first solution group. Separately measure 5g of succinimide polysaccharide and dissolve in 60ml of purified water to obtain the second solution group. Place the reserved area of the pre-treated prosthesis obtained in step 2 flat in a wide-mouthed container. Pour the mixture of the first and second solutions into the wide-mouthed container and cover the reserved area of the pre-treated prosthesis to form a reaction system. Place the above reaction system in an ultrasonic agitator to accelerate the solution wetting and cross-linking reaction. Stop the reaction after 1 hour. Remove excess material along the edge contour of the pre-treated prosthesis, allowing the cross-linked gel to fill the microporous structure of the reserved area to form a composite part. The cross-linked gel extends 0.8cm outward from the edge of the pre-treated prosthesis to form a gel part, obtaining the cranioplasty implant.
[0174] 6. The skull repair implant obtained in step 5 is subjected to irradiation sterilization to ensure a sterile state, thus obtaining the skull repair implant product.
[0175] Comparative Example 4
[0176] 1. Based on the information of the pig skull defect, a PEEK elliptical prosthesis (60mm×50mm, circumference 35.4cm) with matching contour and arc height structure was mechanically prepared as the base. Based on the design requirements, a 0.8cm long reserve was made at the position where the entire edge of the PEEK elliptical prosthesis extends towards the center, forming a reserved area.
[0177] 2. The reserved area of the PEEK elliptical prosthesis was immersed in a 98% concentrated sulfuric acid solution and sonicated for 15 minutes. After removal, it was alternately rinsed, sonicated, and soaked with purified water and 0.1 mol / L sodium hydroxide solution to remove sulfuric acid residue. Finally, it was thoroughly rinsed with purified water and dried for later use, forming a porous region with multiple microporous structures. Optical microscopy showed that the average pore size of the microporous structure was 5 μm. The surface area of the porous region was approximately 80% of the surface area of the substrate, thus obtaining the pretreated prosthesis.
[0178] 3. Measure 3g of bioactive glass particles with a particle size of approximately 0.3μm (after grinding and sieving), and 10g of gelatin particles. Disperse them together in 45ml of purified aqueous solution. Heat to 37℃ and stir mechanically until the gelatin is completely dissolved and the solution is in an emulsion state to obtain a gelatin-bioactive glass particle mixed solution. Separately, measure 0.5g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDC) and disperse it in 5ml of purified water. After complete dissolution, obtain an EDC solution. Add the EDC solution dropwise to the gelatin-bioactive glass particle mixed solution and stop the reaction after 5min. At this time, the solution is in a continuous gel state, and the cross-linked product is obtained.
[0179] 4. Place the cross-linked product obtained in step 3 into 1000 ml of purified aqueous solution. After full swelling, perform physical cutting and pulverization. After pulverization, soak the product three times with 75% alcohol and centrifuge to settle it. Then freeze-dry the product and perform physical pulverization twice. After sieving, retain particles with a particle size of 0.3 to 0.7 μm, which is the first component, for later use.
[0180] 5. Weigh 2.6g of the first component obtained in step 4, and separately measure 6.6g of gelatin. Dissolve them together in 33ml of purified water to obtain the first solution. Separately measure 5g of aldehyde-modified polysaccharide and dissolve it in 33ml of purified water to obtain the second solution. Place the reserved area of the pre-treated prosthesis obtained in step 2 flat in a wide-mouthed container. Pour the mixture of the first and second solutions into the wide-mouthed container and cover the reserved area of the pre-treated prosthesis to form a reaction system. Place the above reaction system in an ultrasonic oscillation to accelerate the solution wetting and cross-linking reaction. Stop the reaction after 1 hour. Remove excess material along the edge contour of the pre-treated prosthesis, allowing the cross-linked gel to fill the microporous structure of the reserved area to form a composite part. The cross-linked gel extends 0.5cm outward from the edge of the pre-treated prosthesis to form a gel part, thus obtaining the cranioplasty implant.
[0181] 6. The skull repair implant obtained in step 5 is subjected to irradiation sterilization to ensure a sterile state, thus obtaining the skull repair implant product.
[0182] Performance testing
[0183] 1. Animal implantation trial evaluation
[0184] The cranial repair implants from Examples 1-5 and Comparative Examples 1-4 were used for implantation trials. The specific steps were as follows: a defect was created based on the prosthesis structure, and surgery was performed on Bama miniature pigs. The cranial repair implants from Examples 1-5 and Comparative Examples 1-4 were aseptically treated and then implanted into the defect site. The skin was then sutured. Anatomical observation was performed six months later.
[0185] The results showed that the gel portion of the cranioplasty implants in Examples 1-5 and Comparative Examples 1-4 was completely degraded, and new bone could grow into the edge of the cranioplasty implant.
[0186] 2. Adhesion test
[0187] Based on the animal implantation experiments completed above, the anatomical structure connected to the pig skull bone window was used for adhesion testing.
[0188] A high-strength metal wire with a diameter of 2mm is passed through two adjacent through holes in the main body of the cranioplasty implant to form a clamping point perpendicular to the cranioplasty implant and clamped onto the test fixture of the universal testing machine.
[0189] The base is fixed to the base of the universal testing machine by a clamp;
[0190] The universal testing machine was set to tensile test mode. The adhesion force was evaluated by moving the test end of the universal testing machine. The test was stopped and the maximum value was recorded after the cranial repair implant product was separated from the pig skull bone window.
[0191] The obtained maximum force value was normalized to the perimeter of the cranioplasty implant product to obtain the average adhesion force per centimeter, as shown in Table 1 below.
[0192] 3. Static compression force test
[0193] An elliptical test platform with a diameter of 55 mm × 45 mm was prepared using polyaryletherketone materials.
[0194] Place the cranioplasty implant product that has completed the above adhesion test on the elliptical test platform;
[0195] Set the universal testing machine to compression test mode and select a 5mm spherical indenter for compression test;
[0196] When the cranioplasty implant product fractured and bent, the test was stopped, and the maximum value was recorded. The results are shown in Table 1.
[0197] Table 1
[0198] Example 1 15.17 685 Example 2 15.08 592 Example 3 14.35 491 Example 4 14.29 425 Example 5 14.21 393 Comparative Example 1 9.94 423 Comparative Example 2 12.01 654 Comparative Example 3 12.29 280 Comparative Example 4 14.89 275
[0199] As shown in Table 1, the cranioplasty implants in Examples 1-5 exhibit suitable adhesion and static compressive strength, effectively fixing the defect structure and meeting clinically required repair strength. Comparative Example 1 has a lower average adhesion force, failing to effectively fix the defect structure. Comparative Examples 2-3 have slightly lower average adhesion forces, posing a risk of instability during defect fixation. Comparative Example 4 has a lower static compressive strength, posing a risk that the repair strength may not meet clinical requirements during defect repair.
[0200] 4. Swelling degree test
[0201] The morphological stability of gels in cranioplasty implants under in vivo physiological conditions is crucial for maintaining their adhesion and fixation. Swelling of the gel can affect its mechanical stability and structural integrity; therefore, low swelling or even no swelling is required during cranioplasty.
[0202] Swelling degree experiments were conducted on the gels of the cranioplasty implants of Examples 1-5 and Comparative Examples 1-4. At least 1g of the gel of the cranioplasty implant was taken for testing, and the initial gel volume was recorded as V0. After soaking in purified aqueous solution for 24 hours, the gel volume was recorded as V1. The swelling degree was then calculated according to the following formula (I), and the results are shown in Table 2 below.
[0203] Swelling rate = V1 / V2 × 100% (I)
[0204] Table 2
[0205] Example 1 97 Example 2 106 Example 3 105 Example 4 103 Example 5 104 Comparative Example 1 98 Comparative Example 2 176 Comparative Example 3 104 Comparative Example 4 127
[0206] As can be seen from Table 2, the swelling degree of the gel of the cranioplasty implants in Examples 1-5 was about 100% after soaking for 24 hours, indicating that the gel in the cranioplasty implants of the present invention was almost completely non-swelling and had a relatively stable network structure; while the swelling degrees of the cranioplasty implants in Comparative Examples 2 and 4 were 176% and 127% respectively after soaking for 24 hours, which could not meet the needs of clinical use.
[0207] It should be noted that although the technical solution of the present invention has been described with specific examples, those skilled in the art will understand that the present invention should not be limited thereto.
[0208] The various embodiments of the present invention have been described above. These descriptions are exemplary and not exhaustive, nor are they limited to the disclosed embodiments. Many modifications and variations will be apparent to those skilled in the art without departing from the scope and spirit of the described embodiments. The terminology used herein is chosen to best explain the principles, practical application, or technical improvements to the embodiments in the market, or to enable others skilled in the art to understand the embodiments disclosed herein.
Claims
1. A cranial repair implant, characterized in that, The cranioplasty implant includes a main body made of polyaryletherketone and has a through-hole; wherein... The area extending within 1 cm from the edge of the main body towards its center is a porous region. The area of the upper surface of this porous region is 10% to 70% of the upper surface area of the main body. This porous region has multiple microporous structures, allowing the gel to fill these microporous structures to form a composite part. The gel extends beyond the edge of the main body to form a gel portion; The raw materials of the gel include a first component, a second component, and a third component; wherein, the first component includes gelatin-encapsulated bioactive particles, and the surface of the first component contains primary amino and / or carboxyl groups; the second component includes biodegradable materials with primary amino groups; and the third component includes polysaccharides with functionalized groups. The mass ratio of the second component to the third component is (0.8~2):
1.
2. The cranioplasty implant according to claim 1, characterized in that, The average pore size of the microporous structure is 0.5~5μm.
3. The cranioplasty implant according to claim 1 or 2, characterized in that, The bioactive particles have a particle size of 0.1~3.0 μm; The second component includes one or more of gelatin, polyethyleneimine, or polylysine; The functionalized groups include aldehyde groups and / or succinimide groups.
4. The cranioplasty implant according to claim 3, characterized in that, By mass, the ratio of the content of the first component to the sum of the contents of the second and third components is (3~7):(10~20).
5. A method for preparing a cranioplasty implant according to any one of claims 1-4, characterized in that, Includes the following steps: Step 1: A reserved area is formed within 1 cm from the edge of the skull repair matrix containing polyaryletherketone material to the center, and the reserved area of the matrix is pretreated to form a microporous structure to obtain a pretreated product. Step 2: Fill the microporous structure of the reserved area with gel to form a composite part; Step 3: Extend the gel beyond the edge of the substrate to form a gel portion, thereby obtaining a cranial repair implant.
6. The preparation method according to claim 5, characterized in that, The pretreatment includes the steps of sulfonation and / or plasma treatment of the reserved area of the substrate.
7. The preparation method according to claim 6, characterized in that, The pretreatment includes placing the reserved area in a sulfuric acid solution for sulfonation.
8. The preparation method according to claim 7, characterized in that, The sulfonation treatment time is 1 to 10 minutes, and the concentration of the sulfuric acid solution is above 95%.
9. The preparation method according to any one of claims 5-8, characterized in that, Step 2 includes: The first component and the second component are dissolved in a first solvent to obtain a first group of solutions, wherein the first component and / or the second component has a primary amino group; The third component is dissolved in the second solvent to obtain the second solution, wherein the third component has functionalized groups; The first group of solutions was mixed with the second group of solutions to obtain a mixed solution; The mixed solution is present in the reserved area and undergoes a cross-linking reaction, so that the gel fills the microporous structure of the reserved area to form a composite part.
10. The preparation method according to claim 9, characterized in that, The molar concentration of primary amino groups in the first group of solutions is not greater than the molar concentration of functionalized groups in the second group of solutions.
11. The preparation method according to claim 10, characterized in that, The molar concentration ratio of primary amino groups in the first group of solutions to functionalized groups in the second group of solutions is 1:(1~3.5).
12. The preparation method according to claim 11, characterized in that, The molar concentration ratio of primary amino groups in the first group of solutions to functionalized groups in the second group of solutions is 1:(1.2~1.4).
13. The preparation method according to claim 9, characterized in that, The cross-linking reaction takes 0.5 to 2 hours.
14. The preparation method according to claim 9, characterized in that, The preparation method of the first component includes the following steps: Gelatin and bioactive particles are dissolved in a third solvent to obtain a gelatin-bioactive particle mixed solution; The gelatin-bioactive particle mixture solution was cross-linked using a cross-linking agent to obtain a cross-linked product; The cross-linked product is pulverized and then freeze-dried to obtain particulate matter, which is the first component.
15. The preparation method according to claim 14, characterized in that, The crosslinking treatment time is 1~10 min.
16. The preparation method according to claim 14, characterized in that, In the gelatin-bioactive particle mixed solution, the mass concentration of the bioactive particles is 1%~20%, and the mass concentration of the gelatin is 5%~30%; based on the total mass of the gelatin-bioactive particle mixed solution as 100%, the amount of crosslinking agent added is 0.1%~5%.
17. A cranioplasty system, characterized in that, Including the cranioplasty implant and bone adhesive according to any one of claims 1-4.
18. The cranioplasty system according to claim 17, characterized in that, The bone adhesive comprises one or more of aldehyde-modified polysaccharides, succinimide-modified polysaccharides, or biodegradable or non-biodegradable cyanoacrylate adhesives.
Citation Information
Patent Citations
Bone repair material, preparation method thereof and cranio-maxillofacial repair prosthesis
CN112773933A
Devices and methods for treatment of facet and other joints
US9308091B2